It was inhaled not swallowed-Neglected 5 month foreign body airway - R, Senthilraj; S, Amarpreet; S, Periyathamby; NFH, Nik Hassan (Bangladesh Journal of Medical Science, 2019)
A delayed detection of foreign body airway implicated high morbidity. The longer duration of the foreign body in the lung can lead to a more sinister complication. A radiolucent foreign body, non organic foreign body and unwitnessed foreign body ingestion contribute significantly to the delay in the diagnosis of foreign body aspiration. We report a case of an undiagnosed radio opaque foreign body in the right bronchus for five months in a 8-year-old child, which the onset of foreign body ingestion was witnessed by parents. Eventually he presented with pneumonia and atelectasis. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.820-822